Surface roughness in drilled carbon fiber reinforced polymer (CFRP)composite using diamond coated ball-nose drills - Konneh, Mohamed; Sudin, Izman; Sidek, Atiah Abdullah; Salleh, Muhammad Salahuddin (Trans Tech Publications Ltd., Switzerland, 2015)
This paper discusses an experimental investigation into the influence of machining parameters on surface roughness when drilling CFRP using 4 mm-diameter 2-fluted carbide drills coated with diamond. The experimental plan employed in this study is based on Central Composite Design technique, established considering drilling with prefixed cutting parameters in a locally prepared Carbon Fiber-Reinforced Plastic (CFRP) composite material by hand lay-up technique using diamond coated carbide twist drills. A model using multiple regression analysis between rotational speed and feed rate with the surface roughness (Ra) of the fiber reinforced laminates has been predicted for the machining conditions investigated. It has been found that the lowest surface roughness Ra (0.910 μm) was generated at rotational speed, 5062 rpm and feed rate, 180 mm/min; and the highest surface roughness Ra (4.630 μm) generated at a rotational speed of 537 rpm and feed rate of 180 mm/min.